Manajemen Pendidikan Islam Melalui Pendekatan Interdisipliner - Zaskia Zaskia (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Advances in knowledge and the increasingly complex demands of contemporary education necessitate innovative approaches to the management of Islamic educational institutions. Islamic Education Management can no longer rely on a single disciplinary perspective; instead, it requires an interdisciplinary framework that integrates management theory, sociology, educational psychology, and Islamic studies. This study aims to examine the significance of an interdisciplinary approach in enhancing the effectiveness of Islamic Education Management, particularly in the areas of planning, organizing, leadership, and academic supervision. Employing a qualitative library research method, this study analyzes primary and secondary sources, including indexed journal articles, educational management literature, and contemporary Islamic references. The findings indicate that interdisciplinary integration strengthens institutional governance, promotes cross-functional collaboration, and enhances institutional adaptability to social and technological changes. Furthermore, this approach contributes to the development of more holistic and contextually relevant managerial strategies. Therefore, the implementation of an interdisciplinary approach in Islamic Education Management is proven to be effective in improving institutional quality, fostering instructional innovation, and enhancing readiness to face the challenges of 21st-century education.